Згода одного з подружжя на вчинення правочинів щодо спільного майна - Д’ячкова, Н. А.; Dyachkova, N. A.; ORCID: http://orcid.org/0000-0003-4117-5432; Тучин, Ф. А.; Tuchyn, F. A. (Право і безпека. - 2015. - № 2 (57). - С. 160-165., 2015)
Досліджено питання правової природи згоди одного з подружжя на вчинення правочинів щодо спільного майна другим із подружжя. Розглянуто проблеми надання такої згоди у різних видах договорів. Надано пропозиції щодо удосконалення практики застовування чинного законодавства.

The issue of the legal nature of the consent provided by another spouse to commit a transaction by another spouse concerning the joint property is one of the least studied matters in jurisprudence. Nowadays, there is no research on the legal nature of consent in the modern science of family, which significantly complicates the correct understanding of the consent as a family and legal category. The authors of the article deal with the issue concerning the legal nature of the consent within family law as a way to implement the subjective rights unilaterally belonging to a person and how to protect the rights of the spouse who is not a title holder and is not directly involved in the contract. The authors have analyzed difference of parental consent to commit a transaction by their minor child from the consent of a spouse to commit a transaction by another spouse concerning the joint property. It is proved that by providing prior consent to commit a transaction concerning the joint property by one of the spouses the law protects the rights of the spouse who is not a title holder and is not directly involved in the contract. The concept «valuable marital property», which includes also money, is studied; and it is offered to consider agreements to acquire things having significant value as transactions on valuable marital property. The authors have grounded the conclusion that small household transaction committed by one of the spouses without the consent of another one, can also be contested in a court. To determine the legal consequences of an agreement on joint property disposal must establish «the fact of disagreement» of one of the spouses on concluding the agreement by another spouse, and not «the fact of presence or absence» of such a consent; notarized consent of another spouse is required for agreements of free property disposal, etc.

Исследованы вопросы правовой природы согласия одного из супругов на совершение сделок в отношении общего имущества другим супругом. Рассмотрены проблемы предоставления такого согласия в разных видах договоров. Даны предложения по усовершенствованию практики применения действующего законодательства.
Dyachkova, N.A. and Tuchin, F.A. (2015), “The spousal consent to commit transactions concerning the joint property” [“Zhoda odnoho z podruzhzhia na vchynennia pravochyniv shchodo spilnoho maina”], Pravo i Bezpeka, No. 2, pp. 160–165.
Д’ячкова, Н. А. Згода одного з подружжя на вчинення правочинів щодо спільного майна / Н. А. Д’ячкова, Ф. А. Тучин // Право і безпека. - 2015. - № 2 (57). - С. 160-165.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; згода одного з подружжя; спільне майно подружжя; правочини подружжя; цінне майно; дрібний побутовий правочин; spousal consent; joint property of the spouses; transactions of spouses; valuable property; small household transaction; согласие одного из супругов; общее имущество супругов; сделки супругов; ценное имущество; мелкая бытовая сделка